Analisis Keterlibatan Faktor Demografi Pada Niat Menjadi Nasabah Bank Syariah - Nurtantiono, Andri (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
The study objective was to determine the involvement of factors Age, Gender, Level of Education and Income on the influence of attitudes, subjective norms and perceived behavioral control on the intention of the business to customers of Islamic banks in Surakarta. The study design used in the design of the survey population SME business in the city of Surakarta with a sample of 100 businesses. Of the four demographic variables are Age, Gender, Education and Income, Education Levels only a moderate influence of Attitude, Subjective norms and perceived behavioral control to the customers intention to Islamic banks. Education has an individual doing a lot more consideration, in which 1) the intent to influence customer attitudes will be stronger when business people are more educated than when businesses less educated, 2) Subjective norms influence a customers intentions will be stronger when businesses less educated than when businesses are more educated and 3) the effect of perceived behavioral control on the intention to clients will be stronger when business people less educated than when businesses better educated.